Modelling of Mechanical Properties of Metal Plates with Polymer Coatings (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this work, we compare the experimental and calculated results obtained in the numerical simulation of uniaxial tension of specimens of metal plates with a thickness of 0.7 mm. For modeling, the Digimat-FE (MSC) system was used, which in numerical calculations uses the finite element solver of the Marc software package (MSC). It is shown that for samples without coatings, the found theoretical values of the critical load quite well correspond to the points on the experimental diagrams at which the dependence of the load and displacement ceases to be linear. For specimens with coatings, the critical loads are significantly lower, and for their description it is necessary to obtain a refined estimate taking into account the effect of residual stresses.